KEMAMPUAN GURU DALAM MENGELOLA KELAS DI MIN SIBUHUAN - Faridah Sa’diyah Hasibuan (JURNAL PENDIDIKAN DAN KEGURUAN, 2024)
Seeing how important it is to manage this class, the author is interested in exploring further how teachers can develop more dynamic classes to achieve the expected goals. For that, the author tries to research: "Teacher Ability in Managing Classes at MIN Sibuhuan" in a research paper. Teacher Ability in Managing Classes at MIN Sibuhuan in using learning methods is still monotonous, teachers still use lecture and question and answer methods without interspersed with other methods. However, when viewed from the arrangement of the room, seating, teaching tools, class beautification, managing student absences has been done well. The teacher's obstacles in managing classes at MIN Sibuhuan are: The teacher's monotonous method in delivering material makes students bored and fed up; students who do not obey the rules and come in and out of class when the teacher is explaining the lesson. Lack of facilities, such as student handbooks with a sharing system and broken tables and chairs, making it difficult for students to follow the lesson properly.